Both Quantity and Quality of Antenatal Care Matter for Child Birthweight: An Analysis of Nationally Representative Data From Bangladesh, India, Nepal, and Pakistan. (7th June 2021) - Neupane, Sumanta; Scott, Samuel; Nguyen, Phuong; Menon, Purnima
Abstract: Objectives: Antenatal care (ANC) is an important platform to deliver health and nutrition interventions during pregnancy but there is limited evidence on how both the number and content of ANC visits relate to birth outcomes. We examined the independent and additive contributions of ANC quantity and quality on child birthweight in four South Asian countries. Methods: We used Demographic and Health Surveys for mothers of children with birthweight data from Bangladesh (2018; n = 2, 279), India (2016; n = 147, 762), Nepal (2016; n = 2, 618) and Pakistan (2017; n = 1, 621). We assessed number of ANC visits and ANC quality using a set of 11 health and nutrition intervention indicators (e.g., weight and blood pressure measurement, urine sample collection, ultrasound, nutrition education). Each country had different indicators available, so we generated country-specific dummies for high ANC quality (woman received more than half of interventions). We categorized mothers into 4 groups: 1) low quantity (<4 ANC visits) and low quality, 2) high quantity (≥4 ANC visits) and low quality, 3) low quantity and high quality, 4) high quantity and high quality. For each country, we ran a logistic regression with low birthweight (LBW; <2500 grams) as the outcome and the 4-group quantity/quality indicator as the main predictor of interest. To test for bias in the subsample with birthweight data, we reran models using the outcome of perceived birth size on the full sample. All models adjusted for child age and sex, woman's age, education, and household socioeconomic status. Results: Both high quantity and high-quality ANC were reported most often by women in Nepal (42.9%), followed by Pakistan (32.0%), Bangladesh (26.6%) and India (21.8%). Compared to women reporting both low quantity and low quality, women who reported high quantity and high quality had lower odds of giving birth to a LBW child in India (OR = 0.83, 95% CI = 0.78–0.88), Nepal (0.58, 0.39–0.86) and Pakistan (0.43, 0.22–0.81). In 3 of 4 countries, only high quantity or only high quality were not protective against child LBW. We found similar results with the outcome of perceived birth size. Conclusions: ANC quantity and quality are both important for optimal pregnancy and birth outcomes. Frequent low-quality ANC visits or infrequent high-quality ANC visits do not protect children from risk of LBW. Funding Sources: Bill and Melinda Gates Foundation.